Preparação para performance de música de câmara com violão: o uso do corpo no repertório com técnicas estendidas - Mello, Felipe Marques de [UNESP] (2015)
The present work consists of a study on body preparation for chamber music performance with guitar on repertoire with extended techniques. The used methodology is based on a literary review of four themes presented throughoutthis work: 1 - preparation for chamber music performance, 2 - thoughts regarding chamber repertoire for guitar, 3 - thoughts regarding extended techniques and 4 - studies on the use of the body in performances. Moreover, some rehearsal techniques utilized by theauthors in the literary review were also addressed on a more specific manner, relating its importance with a focus on body preparation, such as: 1 - reading 2 - memorization,and 3 - gestural communication. Finally, a guide for performance preparation of three chamber repertoire pieces with guitar containing extended techniques was suggested, being such works: 1 - Musica da Camera, from HansMartin Linde, 2 - Gruselgeschichten, from Heinz Kratochwil, and 3 - Motets, from Arthur Kampela. Thus, approaches concerning extended techniques and musical performance preparation regarding each piece were addressed focusing on body preparation